2012
DOI: 10.1007/s10456-012-9263-3
|View full text |Cite
|
Sign up to set email alerts
|

A vaccine targeting angiomotin induces an antibody response which alters tumor vessel permeability and hampers the growth of established tumors

Abstract: Angiomotin (Amot) is one of several identified angiostatin receptors expressed by the endothelia of angiogenic tissues. We have shown that a DNA vaccine targeting Amot overcome immune tolerance and induce an antibody response that hampers the progression of incipient tumors. Following our observation of increased Amot expression on tumor endothelia concomitant with the progression from pre-neoplastic lesions to full-fledged carcinoma, we evaluated the effect of anti-Amot vaccination on clinically evident tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…Conversely, we observed for treated mice an increase of voxels showing medium K trans and v p values in the central region of tumor (set #2 for a three-group subdivision, Figure 3). The increased values of tumor K trans and v p in specific tumor sub-regions correctly reflected previous findings of histological and immunofluorescence analysis, where vascular morphology and vessel permeability were shown to be markedly changed in pAmot-treated tumors [45]. The effect of an enhanced microvasculature permeability following the antiangiogenic treatment has already been reported in several cases, a process known as vasculature normalization [49].…”
Section: Dce-mri Has Been Used In the Last Decades In A Numbersupporting
confidence: 87%
“…Conversely, we observed for treated mice an increase of voxels showing medium K trans and v p values in the central region of tumor (set #2 for a three-group subdivision, Figure 3). The increased values of tumor K trans and v p in specific tumor sub-regions correctly reflected previous findings of histological and immunofluorescence analysis, where vascular morphology and vessel permeability were shown to be markedly changed in pAmot-treated tumors [45]. The effect of an enhanced microvasculature permeability following the antiangiogenic treatment has already been reported in several cases, a process known as vasculature normalization [49].…”
Section: Dce-mri Has Been Used In the Last Decades In A Numbersupporting
confidence: 87%
“…Vaccinated females were then mated with a BALBneuT male and neu C offspring was evaluated for mammary tumor development. We have previously shown that vaccinationinduced anti-Amot antibodies impair tumor vascularization 26 and significantly delay autochthonous tumor progression 27 in female BALB-neuT mice. Post-vaccination anti-Amot antibody induction was confirmed in pAmot-vaccinated mother sera and milk as well as in the sera of their offspring (pAmot offspring) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…24) BALB/c mice were maintained at the Molecular Biotechnology Center, University of Torin, and treated in accordance with the University Ethical Committee and European guidelines under Directive 2010/63. Vaccination, performed either before or after tumor challenge, consisted of two intramuscular electroporations at 2 weeks interval, of pVAX1 or pVAX1-xCT plasmids as previously described (25).…”
Section: In Vivo Treatmentsmentioning
confidence: 99%